High prevalence of hypovitaminosis D in postmenopausal women with type 2 Diabetes Mellitus - Raška, Ivan; Rašková, Mária; Zikán, Vít; Škrha, Jan (Prague Medical Report, 2016)
The link between vitamin D and type 2 diabetes mellitus (T2DM) is intensively studied. This study aims to define the serum concentration of 25-hydroxyvitamin D (25-OH D) and to investigate the relationship between 25-OH D status, glycated hemoglobin (HbA1c) and body composition in postmenopausal women with T2DM and in non-diabetic controls. In this cross-sectional study, 75 women with T2DM and 32 control subjects were selected. Serum 25-OH D, intact parathyroid hormone (PTH), calcium, fasting glucose and HbA1c, were measured. The mean 25-OH D level was 21.4±11.4 ng/ml (range 4.1-50.7 ng/ml) in diabetic women and 30.3±9.4 ng/ml (range 10.8-54.2 ng/ml) in control group (p<0.001). The prevalence of hypovitaminosis D (<30 ng/ml) was higher in vitamin D3 non-supplemented T2DM women (89% vs. 63% controls); the difference diminished in vitamin D3 (500-1000 IU per day) supplemented subgroups (45% diabetics vs. 42% controls). In T2DM women, 25-OH D levels were not associated to HbA1c, duration of diabetes, fasting glucose and PTH levels, however, 25-OH D levels negatively associated with body mass index (p=0.011), total body fat mass (p=0.005) and total body lean mass (p=0.004). The prevalence of hypovitaminosis D is higher in non-supplemented postmenopausal women with T2DM than in non-diabetic controls (89% vs. 63%). Obesity is a risk factor for vitamin D insufficiency in T2DM postmenopausal women. Further studies evaluating relationships between fat, muscle, bone and vitamin D metabolism in T2DM patients are warranted.
Keywords: absorpční fotometrie; Female; Prevalence; Absorptiometry, Photon; ženské pohlaví; průřezové studie; postmenopauza; Diabetes Mellitus, Type 2; Obesity; lidé; vitamin D; nedostatek vitaminu D; diabetes mellitus 2. typu; Vitamin D; Risk Factors; prevalence; Cross-Sectional Studies; obezita; složení těla; Aged; Czech Republic; index tělesné hmotnosti; Vitamin D Deficiency; glykovaný hemoglobin; rizikové faktory; Body Composition; Česká republika; lidé středního věku; senioři; Postmenopause; Body Mass Index; Glycated Hemoglobin; Middle Aged; Humans